PERUBAHAN PERAN DAN FUNGSI HULA-HULA PADA TATA CARA PERKAWINAN BATAK TOBA PERANTAUAN DI KECAMATAN TAMPAN PEKANBARU - Sihombing, Natanael Junjungan; Hambali, Hambali; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the Changing Roles and Functions of Hula-Hula in the Procedure of Overseas Batak Toba Marriage in Tampan District, Pekanbaru. Considering that the Hula hula is one of the social elements that has the highest or more privileged position in the structure of the dalihan na tolu, which is the group of people from which our mother is born and is a group of people whose position is highly respected, there is an expression that says somba marhula-hula which means respect for the hula-hula in order to obtain safety and prosperity. This research method uses mixed methods. Mechanical collectionof data used is questionnaire , documentary and literature study , interview. This research was conducted in the Tampan District, Pekanbaru. Amount of population in the study of this is the 3899 Head of the Family . The sample in the study were taken by purposive sampling, of the population is taken as a source of data that can represent the entire population, as many as 30 head of family The results showed that Changes Role and Functions of Hula-hula on the Marriage Procedure in the district of Toba Batak Overseas Handsome Pekanbaru are at levels that are very low, which amounted to 11.39 % . where the range of extremely low are at 0 % - 20 %. This is influenced by internal factors and external factors. Internal factors are new ideas to replace existing tools (innovations) and inter-group conflicts in society. Then the external factor is getting influence from other communities. In addition there are also factors that cause changes in the marriage tradition. First, the economy of each community is different. Secondly, the time spent at the wedding ceremony is quite long.Key Words: Change, Role and Function of Hula-hula, The Procedure for the Marriage of the Batak Toba Tribe